Rubrics for assessing student achievement in science, grades K-12 - Lantz, Hays B. (Thousand Oaks, CA : Corwin Press, 2004)
Presents a collection of evaluation and assessment tools teachers may use to track the progress of students from kindergarten through twelfth grade in science, including performance lists, as well as holistic and analytic rubrics.
Includes bibliographical references (p. 189) and index.
The Science Teacher (N.S.T.A.).
Professional
Keywords: Science -- Examinations, questions, etc; Science -- Study and teaching (Elementary) -- United States -- Evaluation; Science -- Study and teaching (Secondary) -- United States -- Evaluation; Science -- Examinations; Science -- Study and teaching -- Evaluation